Active commuting to school and physical activity levels among 11 to 16 year-old adolescents from 63 low- and middle-Income countries - Peralta, Miguel (2020)
© 2020 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (http://creativecommons.org/licenses/by/4.0/).